Research progress on the biosynthesis, metabolic engineering, and pharmacology of bioactive compounds from the Lonicera genus - Xiaojie Chen; Weiqiang Li; Xu Lu; Lam-Son Phan Tran; Raphael N. Alolga; Xiaojian Yin (Medicinal Plant Biology)
The Lonicera genus with medicinal and edible characteristics is a rich source of bioactive compounds that together account for numerous health benefits. Plants within this genus have been used traditionally in China to treat heat-related illnesses, viral respiratory infections, skin diseases, and inflammation for thousands of years. The main bioactive compounds include chlorogenic acids, flavonoids, iridoids, and triterpene saponins. Aside from the role of this genus as a valuable medicinal resource, constituent members have also been used in the food and cosmetic industries. Due to the huge demand for plants within the Lonicera genus, and the propensity for overexploitation of the wild resources of Lonicera, there is a need to meet this demand via alternative and efficient strategies such as metabolic engineering and green production. Here, we provide a comprehensive review of relevant scientific literature covering the structure, biosynthesis, metabolic engineering, pharmacology and phylogenetic analysis of the main bioactive constituents of the Lonicera genus. Finally, we proffer suggestions on the prospects of fully exploiting and utilizing plants of the Lonicera genus as useful medicinal plant resources.